A Duplication Upstream of SOX9 Associated with SRY Negative 46,XX Ovotesticular Disorder of Sex Development: A Case Report - Eda Mengen; Gülsüm Kayhan; Pınar Kocaay; Seyit Ahmet Uçaktürk (Galenos Yayincilik, 2020)
The 46,XX ovotesticular disorder of sex development (DSD) is rarely observed in humans. This disorder is generally described as ambiguous genitalia with the presence of ovarian and testicular tissues in different gonads or in the same gonad. Almost no subjects with 46,XX ovotesticular DSD have sex-determining region of the Y chromosome (SRY) gene. It is known that excessive expression of SRY-related high mobility group box 9 (SOX9) is the cause of SRY-negative 46,XX ovotesticular DSD in the absence of SRY. Here, we analyzed our SRY-negative case with 46,XX ovotesticular DSD. In an array comparative genomic hybridization study using a peripheral blood sample from the patient, a duplication of 1114 kb (Hg19 coordinates: chr17:69006280-70120619) in the region of 17q24.3 containing SOX9 was detected. This is the first case reported from Turkey, exhibiting SOX9 duplication in SRY-negative 46,XX ovotesticular DSD.